IMPLEMENTASI KEBIJAKAN PENDIDIKAN ISLAM DI MA MAMBAUL ULUM SERPONG - Khodijah Khodijah; Mahliga Fitriyansah; Hasan Basri; Andi Hidayat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the implementation of Islamic education policies at MA Mambaul Ulum Serpong and identify factors that support and hinder its implementation. Islamic education plays a strategic role in shaping students who excel not only academically but also possess strong religious, moral, and social character. Therefore, the implementation of Islamic education policies in secondary education institutions is a crucial aspect in achieving national education goals and the goals of Islamic education. This study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews with the madrasah principal, teachers, and students, and documentation related to the implementation of Islamic education policies in the madrasah. The results indicate that the implementation of Islamic education policies at MA Mambaul Ulum Serpong is realized through the integration of Islamic values ​​into the learning process, the introduction of religious activities, the strengthening of character education, and the implementation of a religious madrasah culture. Programs such as congregational prayer, Quran recitation, commemoration of Islamic holidays, and extracurricular religious activities are important in supporting the implementation of these policies. Supporting factors for policy implementation include the commitment of madrasah leadership, the competence of teaching staff, parental support, and the availability of adequate facilities and infrastructure. Meanwhile, inhibiting factors identified include differences in student backgrounds, limited learning time, and the influence of technological developments and the social environment.